Lutein, a carotenoid, suppresses osteoclastic bone resorption and stimulates bone formation in cultures. Issue 2 (1st February 2017) - Tominari, Tsukasa; Matsumoto, Chiho; Watanabe, Kenta; Hirata, Michiko; Grundler, Florian M.W.; Inada, Masaki; Miyaura, Chisato
Abstract : Lutein, a member of the xanthophyll family of carotenoids, suppressed IL-1-induced osteoclast differentiation and bone resorption. The survival of mature osteoclasts was also suppressed by lutein in cultures. When lutein was added to the cultures of osteoblasts, lutein enhanced the formation of mineralized bone nodules by elevating BMP2 expression and inhibiting sclerostin expression. Lutein may be beneficial for bone health.